Immunologic Self-Tolerance Maintained by Cd25(+)Cd4(+)Regulatory T Cells Constitutively Expressing Cytotoxic T Lymphocyte–Associated Antigen 4 - Takahashi, Takeshi (The Rockefeller University Press, 2000)
This report shows that cytotoxic T lymphocyte–associated antigen 4 (CTLA-4) plays a key role in T cell–mediated dominant immunologic self-tolerance. In vivo blockade of CTLA-4 for a limited period in normal mice leads to spontaneous development of chronic organ-specific autoimmune diseases, which are immunopathologically similar to human counterparts. In normal naive mice, CTLA-4 is constitutively expressed on CD25(+)CD4(+) T cells, which constitute 5–10% of peripheral CD4(+) T cells. When the CD25(+)CD4(+) T cells are stimulated via the T cell receptor in vitro, they potently suppress antigen-specific and polyclonal activation and proliferation of other T cells, including CTLA-4–deficient T cells, and blockade of CTLA-4 abrogates the suppression. CD28-deficient CD25(+)CD4(+) T cells can also suppress normal T cells, indicating that CD28 is dispensable for activation of the regulatory T cells. Thus, the CD25(+)CD4(+) regulatory T cell population engaged in dominant self-tolerance may require CTLA-4 but not CD28 as a costimulatory molecule for its functional activation. Furthermore, interference with this role of CTLA-4 suffices to elicit autoimmune disease in otherwise normal animals, presumably through affecting CD25(+)CD4(+) T cell–mediated control of self-reactive T cells. This unique function of CTLA-4 could be exploited to potentiate T cell–mediated immunoregulation, and thereby to induce immunologic tolerance or to control autoimmunity.